1995
DOI: 10.1063/1.470492
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and energetics of xenon in mordenite: A Monte Carlo simulation study

Abstract: Grand canonical Monte Carlo (GCMC) simulations were used to calculate energy contour maps, isodensity surfaces and adsorption isotherms of xenon in purely siliceous mordenite at 300 K using previously published potential parameters. Then, in order to understand the effect of aluminum content, Al-containing mordenites were modeled by adding the appropriate negative charge to each of the oxygen atoms in the mordenite framework and by inserting Na+ ions at fixed extra-framework positions previously identified fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
6
13
0
Order By: Relevance
“…Obviously, gas molecules first occupy the smaller tetrahedron‐shaped side pockets (Figure 4a), followed by the saturation of the pockets (Figure 4b), and then they start occupying the positions near the unsaturated Cu atoms as well as the larger square‐shaped channels with further increasing pressure. The similar behavior has also been observed in zeolites such as mordenite with similar topology 37…”
Section: Resultssupporting
confidence: 79%
“…Obviously, gas molecules first occupy the smaller tetrahedron‐shaped side pockets (Figure 4a), followed by the saturation of the pockets (Figure 4b), and then they start occupying the positions near the unsaturated Cu atoms as well as the larger square‐shaped channels with further increasing pressure. The similar behavior has also been observed in zeolites such as mordenite with similar topology 37…”
Section: Resultssupporting
confidence: 79%
“…In the large channel, adsorption at adjacent walls is eliminated for the large probes, and the structure of the large channel forces adsorbate−adsorbent interactions that are energetically unique. The MEA description of adsorption distinguishes between two unique interactions in the large channel for Xe (5.995 ± 0.067 kcal mol -1 for the first process [type 3] and 7.82 ± 0.26 kcal mol -1 for the second process [type 2]), and this finding is in agreement with the Monte Carlo simulations of Xe adsorption on Na− MOR . From Monte Carlo simulations, Nivathi et al conclude that there are two heterogeneous adsorption processesone process at the opening to the side pockets in the main channel (two “sites”) with an enthalpy of 10.7 kcal mol -1 and the other process in the main channel (six “sites”) with an enthalpy of 7.2 kcal mol -1 .…”
Section: Resultssupporting
confidence: 62%
“…The MEA description of adsorption distinguishes between two unique interactions in the large channel for Xe (5.995 ± 0.067 kcal mol -1 for the first process [type 3] and 7.82 ± 0.26 kcal mol -1 for the second process [type 2]), and this finding is in agreement with the Monte Carlo simulations of Xe adsorption on Na− MOR . From Monte Carlo simulations, Nivathi et al conclude that there are two heterogeneous adsorption processesone process at the opening to the side pockets in the main channel (two “sites”) with an enthalpy of 10.7 kcal mol -1 and the other process in the main channel (six “sites”) with an enthalpy of 7.2 kcal mol -1 . The authors state that two of the six “sites” of the main channel have a slightly different adsorption potential, a difference of 0.09 kcal mol -1 for a Si/Al ratio of 5, which is within two standard deviations of the MEA enthalpy for the first process (type 3).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…68 Furthermore, the fraction of the adsorbed methane molecules located in the MOR main channels in the sodium and the pure silica structures was also calculated and the results are given in Figure 9 as a function of the loading. For pure silica structure, it is found that the side pockets are favored but not very strongly because the side pocket adsorption sites have a lower energy 26,69 and the percentage is almost constant with the increasing of the loading. For Na-MOR structure, side pocket adsorption becomes more favorable because the Na cations residing at the opening of the side pockets make these sites more attractive.…”
Section: Results Andmentioning
confidence: 96%